CONTESTATION BETWEEN GLOBAL AND LOCAL IN MANGGARAI RAP MUSIC - Ans. Prawati Yuliantari (Universitas Gadjah Mada, 2016)
Globalization causes the spread of pop culture beyond geographical boundaries. Rap music as a form of pop culture spread around the world in the 1990s through the mass media that was driven by the transnational music industry. Its popularity was not just happened in big cities, but in peripheral regions like in Manggarai of East Nusa Tenggara as well.This article uses the transnational concept in American studies and theory of landscape advanced by Arjun Appadurai. The concept of Transnational American Studies is used to analyze the influence of American culture beyond its territory, while the theory of landscape is used to analyze the conflicts that occured between the global and the local rap music in Manggarai music spaces.This analysis shows that the process of appropriation carried out by local rapper against global rap music is a form of negotiation to adapt to local tastes as well as of creativity to face global music. The strategies undertaken in the struggle for spaces of music can be seen in the form of themes, language, dialect, or mode of production. Contestation between the global and the local is always transformed through the development of music consumers in the area.Keywords: Contestation, Rap, Transnational, Globalization